Muscle strength training is better than the use of growth hormone (Gh) in bone health of wistar rats - Caetano, Heliard Rodrigues Dos Santos; Castoldi, Robson Chacon; Zanuto, Éverton Alex Carvalho; Ozaki, Guilherme Akio Tamura; Garcia, Thiago Alves; Pereira, João Domingos Augusto Dos Santos [UNESP]; Constantino, Carlos José Leopoldo [UNESP]; Bremer-Neto, Hermann; Giometti, Ines Cristina; Camargo, Regina Celi Trindade [UNESP]; Filho, José Carlos Silva Camargo [UNESP]; Belangero, William Dias (My University, 2019)
SUMMARY: The objective of this study was to evaluate the effects of growth hormone (GH) and muscle strength training (ST) on the composition of bone tissue of Wistar rats through Raman spectroscopy. In total, 40 male rats were randomly distributed into four groups: (N = 10) control (C), control with the application of GH (GHC), strength training (T), and strength training with the application of GH (GHT). The training consisted of four series of 10 water jumps, performed three times a week, with an overload corresponding to 50 % of body weight and duration of four weeks. GH was applied at a dose of 0.2 IU / kg in each animal three times a week and every other day. After four weeks, the animals were euthanized and the right femurs collected for analysis of the bone structure. Raman spectroscopy (ER) was used to observe the following compounds from their respective bands: Calcium Carbonate-Triglycerides (fatty acids) 1073 cm -1 , Collagen type I 509 cm -1 , Bone-DNA Phosphate (Protein) 589 cm -1 , Phosphate Phospholipids 1078 cm -1 . For the statistical analysis, the Shapiro-Wilk and ANOVA One-Way variance analysis normality tests were performed, followed by the Tukey post-test. The results showed an increase in the concentrations of calcium carbonate-triglycerides (fatty acids), type I collagen, bone phosphate-DNA (protein), and phosphate phospholipids in all experimental groups, with or without ST and/or GH, But only the isolated training group differed significantly from the control group (P <0.05). It was concluded that all treatments could promote bone tissue gain, however, only the T group demonstrated a significant difference in the mineral compounds analyzed.
Entrenamiento de la fuerza muscular es mejor que el uso de la hormona del crecimiento (Gh) en salud ósea del ratas wistar
Keywords: Calcium carbonate; Collagen; Phosphate; Raman spectroscopy; Swimming